“When less is more and more is less” red cell alloimmunization in multitransfused patients attending a medical institution with a newly developed blood center in North India: A multifactorial study - Ranjan Mukherjee; Gita Negi; Daljit Kaur; Uttam Kumar Nath; Yatendra Chaturvedi; Davood Bava (Asian Journal of Transfusion Science)
INTRODUCTION: Multiple blood transfusions with one or more nonself, genetically mismatched donor red blood cells (RBCs) may result in the production of alloantibodies, complicating future transfusions and increasing patient morbidity. This could be averted if adequate prophylactic measures are implemented in the vulnerable group. Due to the paucity of data in our region, we planned this study to identify the alloimmunization pattern in relation to clinical and demographic patient factors. MATERIALS AND METHODS: A prospective observational study was carried out in a newly developed Medical Institution of National importance in Northern India, for 1 year. The red cell antibody screening and identification were done for 770 patients receiving two or more transfusions. The patient and transfusion-related factors were statistically compared between alloimmunized and nonalloimmunized cases. RESULTS: The overall seroprevalence of RBC alloimmunization among the multi-transfused patients was 4.02% (31/770). Thirty-six alloantibodies were identified in the 31 alloimmunized patients, which comprised 13 different alloantibody specificities. Most of them belonged to the Rh system (38.8%), followed by MNS (25%) and Lewis (27.7%) blood group systems. On Multivariate logistic regression analysis, the highest risk was found to be associated with recipients having more than three transfusions with an odds ratio of 8.4. CONCLUSIONS: The highest alloimmunization risk was found in multi-transfused patients receiving more than three transfusions and with female gender. Rh blood group system was found to be predominating the alloantibody specificity pattern. This highlights the need for the provision of extended Rh (DCcEe) matched packed red cells for susceptible patients.